A Review of Anglo-Indian Identity: Past and Present, in India and the Diaspora - Bera, Shreya (AMERICANA E-journal of American Studies in Hungary, 2021)
Anglo-Indian Identity: Past and Present, in India and the Diaspora Editors: Robyn Andrews, Merin Simi Raj Palgrave Macmillan, Switzerland, 2021 427 pages